THE INFLUENCE OF LEADERSHIP, SUPERVISION AND WORK DISCIPLINE ON TEACHER PERFORMANCE AT TALITAKUM PRIVATE SMP HIGH SCHOOL MEDAN - Elsa Gultom; Yohny Anwar (RADJA PUBLIKA, 2024)
This research was conducted at Talitakum Medan Private Middle School with the aim of finding out how much influence leadership, supervision and work discipline partially and simultaneously have on teacher performance. The population in this study were all employees of the Talitakum Medan Private Middle School, totaling 34 people with the independent variables Leadership, supervision and work discipline while teacher performance was the dependent variable. The method used is a data analysis method using multiple linear regression analysis techniques, classical assumption testing and hypothesis testing. The results of the regression test show that 58.6% of performance factors can be explained by leadership, supervision and work discipline, while the remaining 41.4% is explained by other factors not examined in this research such as work motivation, position, intensity, training and so on. Meanwhile, the results of the f test show that simultaneously leadership, supervision and work discipline together have a significant effect on teacher performance with the results of the tcount analysis (28.229) where ttable is 2.922. The results of the T test show that the leadership variable shows the results of the tcount analysis (2.376), the supervision variable shows the results of the tcount analysis (3.935) and the work discipline variable shows the results of the tcount analysis (3.611) where ttable (1.690). So these three variables have a significant effect on teacher performance at Talitakum Medan Private Middle School.